Increased prevalence of levofloxacin-resistant Mycobacterium tuberculosis in China is associated with specific mutations within the gyrA gene. (March 2020) - Huo, Fengmin; Zhang, Fuzhen; Xue, Yi; Shang, Yuanyuan; Liang, Qian; Ma, Yifeng; Li, Yunxu; Zhao, Liping; Pang, Yu
Highlights: An alarming increase in prevalence of FQ-resistant TB is observed in China over the past decade. This dynamic change in FQ resistance is majorly attributed to the increase of high-level LFX-resistance. A significant difference is noted in the proportion of LFX-resistant isolates harboring specific mutations within gyrA gene between 2005 and 2015. Abstract: Objectives: To compare the prevalence of levofloxacin (LFX) resistance and the population structure of Mycobacterium tuberculosis (MTB) with different mutations conferring LFX resistance between 2005 and 2015. Methods: A total 542 MTB isolates were randomly selected from pulmonary tuberculosis (TB) patients in 2005 and 2015 and analyzed regarding minimum inhibitory concentrations (MICs) and quinolone resistance-determining regions (QRDR). Results: One hundred and eleven of the 542 MTB isolates analyzed (20.5%) were resistant to LFX. There were 42 and 69 LFX-resistant isolates from 2005 and 2015, respectively, and MIC high-level LFX resistance was significantly higher in 2015 (40.6%, 28/69) than in 2005 (16.7%, 7/42) ( p = 0.02). There were 87 (78.4%) mutations of these 111 LFX-resistant isolates. In addition, a significant difference in proportion was observed in the isolates with mutations in codon 90 of the gyrA gene between 2005 and 2015 (11.9% in 2005 versus 29.0% in 2015, p = 0.04). Conclusions: There was an alarming increase in prevalence of LFX-resistant TB in China between 2005 and 2015. This dynamic change is mostly attributed to the increase in high-level LFX resistance. Moreover, a significant difference was noted in the proportion of LFX-resistant isolates harboring specific mutations within the gyrA gene between 2005 and 2015.